Differences Between Mural Art and Graffiti - W. Mohd Apandi, Wan Nurhasyimah (Idealogy Journal, 2018)
Mural art and graffiti art are two forms of visual art that are growing in popularity as a medium and method for visual artists to convey ideas and self-expression through the use of specific materials such as oil paint, acrylic, and spray paint on environmental walls. As a result, this study will go into deeper detail about the distinctions between mural art and graffiti art. Mural art and graffiti art, on the other hand, are significant in society since they are utilized to beautify the surrounding region while also imparting knowledge about a particular subject through the material, images, and text produced by mural painters and graffiti artists. Keyword: Mural Art, Visual Art, and Graffiti